Allergy and occupational exposure to hydroquinone and to methionine. Issue 6 (June 1988) - Choudat, D; Neukirch, F; Brochard, P; Barrat, G; Marsac, J; Conso, F; Philbert, M
Abstract : Respiratory manifestations have been reported after exposure to hydroquinone and to methionine. One hundred and three men in the same chemical plant were divided into three groups according to their exposure and compared by questionnaire, respiratory functional tests with methacholine then salbutamol challenges, and measurements of serum immunoglobulins G and E. Group H included 33 workers exposed to hydroquinone, trimethyl-hydroquinone, and retinene-hydroquinone. Group M included 15 workers exposed to methionine. Group C was a control group of 55 workers. The prevalence of respiratory symptoms was higher in the two exposed groups. Before challenges, pulmonary function values were significantly lower in groups H and M than those in group C. The challenges induced significant variations in the three groups but these variations were less pronounced in group M than in the other groups. The level of immunoglobulin G in group H (m +/- SD = 12.5 gram/liter +/- 2.6) was significantly higher than in group C (10.6 gram/liter +/- 2.4; p less than 0.002). The level of immunoglobulin E in group H (m = 140 IU/l) was also higher in group C (109 IU/l) but this difference was not significant. These findings suggest that exposure to methionine and to hydroquinone and its derivatives induce ventilatory impairment, perhaps by an immunological mechanism.